Valuing the Cultural Monuments of Armenia: Bayesian Updating of Prior Beliefs in Contingent Valuation - Anna Alberini; Alberto Longo (Fondazione Eni Enrico Mattei (FEEM), 2007)
We use contingent valuation to place a value on the conservation of built cultural heritage sites in Armenia. When we present the hypothetical scenario in the questionnaire we spell out what would happen to the monuments in the absence of the government conservation program. We posit that respondents combine such information with their own prior beliefs, which the questionnaire also elicits, and that the WTP for the good or program is likely to be affected by these updated beliefs. We propose a Bayesian updating model of prior beliefs, and empirically implement it using the data from our survey. We find that uncertainty about what would happen to the monument in the absence of the program results in lower WTP amounts.
Keywords: Z10; 330; Valuation of Cultural Heritage Sites; Non-Market Valuation; Contingent Valuation; Bayesian Updating; Prior Beliefs; Kulturökonomik; Bewertung; Kulturgüter; Willingness to pay; Armenien